Prevention behavior of community for spreading COVID-19 in West Kalimantan Province, Indonesia - Linda Suwarni; Selviana selviana; Mawardi Mawardi; Marlenywati Marlenywati; Nilasari Nilasari; Suyitno Suyitno; Maretalinia Maretalinia (Intelektual Pustaka Media Utama, 2021)
The COVID-19 pandemic caused huge impacts on human being worldwide. The accumulated infected cases are 156,778,078 with 3,272,054 death cases on May 7, 2021. Importantly, not many people practice the prevention behavior of COVID-19 pandemic. This study measured the prevention behavior of COVID-19 in West Kalimantan Province, Indonesia by socio-demographic factors and protection motivations from the community. This study used a cross-sectional design which was carried out for two weeks from the end of July to early August. The study involved 385 respondents from 972,635 people in Municipality Pontianak, Municipality Singkawang, and Ketapang Regency, Indonesia. The result showed the majority of the respondent were female (74.3%), in adult age group (61.3%), graduated from university (51.2%), and have a job (64.9%). Multiple logistic regression showed that respondents had no occupation (Adj. OR=1.87, 95% C.I=1.04- 3.37), low perception of self-efficacy (Adj. OR=3.44, 95% C.I=1.98-5.95), and low the evaluated cost response (Adj. OR=1.94, 95% C.I=1.20-3.14) were statistically significant having correlation with poor prevention behavior of spreading COVID-19. The results can be utilized for the promotion of protocol of prevention COVID-19, for instance, provide personal protective equipment (PPE) for people with high-risk occupation including health personal, promote the importance of practice prevention behavior, and control the price of basic PPE including mask and ensure all people have an access to have the mask.